2002
DOI: 10.1124/jpet.102.045260
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of STI-571 to the Brain Is Limited by P-Glycoprotein-Mediated Efflux

Abstract: The adequate distribution of STI-571 (Gleevec) to the central nervous system (CNS) is critical for its effective use in CNS tumors. P-glycoprotein-mediated efflux in the blood-brain barrier may play a role in the CNS delivery of this drug. Whether STI-571 is a substrate of P-glycoprotein was determined by examining the directional flux of [14 C]STI-571 in parental and MDR1-transfected Madin-Darby canine kidney (MDCK) II epithelial cell monolayers. The basolateral-to-apical flux of STI-571 was 39-fold greater t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
180
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(200 citation statements)
references
References 37 publications
14
180
2
1
Order By: Relevance
“…To determine whether an inhibitor of c-Abl protects against the MPTP-induced loss of dopaminergic neurons, we treated animals with STI571, a c-Abl family kinase inhibitor, before or after exposure to MPTP (Figure 2a). It has been shown that intraperitoneally injected STI571 could penetrate into brain, 15 and we confirmed the presence of STI571 in the ventral midbrain by intraperitoneal injection in our experiments (Figure 2b). Moreover, we found that intraperitoneal injection of STI571 did not affect the concentration of MPP + , the metabolite of MPTP, in the striatum (Figure 2c).…”
Section: Resultssupporting
confidence: 88%
“…To determine whether an inhibitor of c-Abl protects against the MPTP-induced loss of dopaminergic neurons, we treated animals with STI571, a c-Abl family kinase inhibitor, before or after exposure to MPTP (Figure 2a). It has been shown that intraperitoneally injected STI571 could penetrate into brain, 15 and we confirmed the presence of STI571 in the ventral midbrain by intraperitoneal injection in our experiments (Figure 2b). Moreover, we found that intraperitoneal injection of STI571 did not affect the concentration of MPP + , the metabolite of MPTP, in the striatum (Figure 2c).…”
Section: Resultssupporting
confidence: 88%
“…It has been reported that IM inhibits the growth of glioma cells in preclinical models, but has poor distribution in the nervous system due to the fact that p-Gp limits its efficacy in patients (14). The results of this study show that CAR provides a synergistic effect on IM-induced cytotoxicity in monolayer and spheroid cultures of malignant C6 glioma cells.…”
Section: Discussionsupporting
confidence: 56%
“…IM has recently been shown to be efficacious in preclinical studies for GBM. Unfortunately, the potential utility of IM has been hampered by problems with drug distribution to the nervous system, as IM is a substrate of P-glycoprotein (p-Gp; the product of MDR1 gene), an active efflux transporter, thus limiting the distribution of IM to the central nervous system (14). Fortunately, the use of p-Gp inhibitors to improve brain penetration of p-Gp substrate drugs has been shown to be effective in both animal and human studies (15).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have confirmed that imatinib interacts with the multidrug transporter proteins, MDR1 (multidrug resistance protein 1, also known as P-glycoprotein) [38][39][40] and MXR (multixenobiotic resistance protein, also known as breast-cancer resistance protein). [41][42][43] Increased expression of these two efflux proteins reduces intracellular concentrations of imatinib and decreases the antiproliferative effects of the drug.…”
Section: Intracellular Imatinib Concentrationsmentioning
confidence: 99%